Modelling polarisation of materials with applications in self-assembly - Williamson, Connor (2025)
Theoretical descriptions of charged induced polarisation and dispersion forces between materials are investigated, extended or applied to study a range of natural and novel environments. Initially, a mathematical framework is established to describe many-body interactions between charged dielectric particles. This framework is then extended to include the effects of inhomogeneous sur- face charge distributions and externally applied electric fields. This extension is rigorously tested against classical results and then further justified for N particles by considering a novel experimentally realised system. The framework is then applied to study the effect of surface charge density and polarisation on the interactions between like-charged particles in noctilucent clouds. Like-charge attraction is shown to promote nucleation of such particles given the possible velocities at the temperature of these environments. Volcanic ash is then investigated in a similar context at the various temperatures it would experience throughout an eruption. Aggregation of volcanic ash due to non-thermal perturbation is also investigated by considering the collisional cross sections of the clouds constituents via particle dynamics. Particle dynamics is then utilised to study the aggregation driven inefficiencies of dry powder inhalers, suggesting a possible method to alleviate this. The electronic interaction of neutral materials at close separation is then investigated in the context of the Casimir force. After an initial bench-marking of a convenient mathematical formalism, new systems in which quantum levitation can be realised are predicted via consideration of the Casimir equilibrium.